2011
DOI: 10.1159/000335112
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates H<sup>+</sup>-ATPase Activity in Intercalated Cells from Isolated Mouse Connecting Tubules and Cortical Collecting Ducts

Abstract: Intercalated cells in the collecting duct system express V-type H+-ATPases which participate in acid extrusion, bicarbonate secretion, and chloride absorption depending on the specific subtype. The activity of H+-ATPases is regulated by acid-base status and several hormones, including angiotensin II and aldosterone. Angiotensin II stimulates chloride absorption mediated by pendrin in type B intercalated cells and this process is energized by the activity of H+-ATPases. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Transepithelial transportation of acid/base equivalents is critical for acid-base regulation and is tightly controlled by various hormones, such as endothelins [39][40][41], angiotensin II [42,43] and corticosteroids [44,45]. By combining molecular, cellular and electrophysiological approaches in the zebrafish model, …”
Section: Discussionmentioning
confidence: 99%
“…Transepithelial transportation of acid/base equivalents is critical for acid-base regulation and is tightly controlled by various hormones, such as endothelins [39][40][41], angiotensin II [42,43] and corticosteroids [44,45]. By combining molecular, cellular and electrophysiological approaches in the zebrafish model, …”
Section: Discussionmentioning
confidence: 99%
“…In the rabbit cortical collecting duct, peritubular ANG II stimulated β cell apical HCO 3-secretion through a basolateral AT1 receptor [105]. In intercalated cells of connecting tubules and cortical collecting ducts, ANG II stimulated H + -ATPase and may have contributed to the regulation of chloride reabsorption and bicarbonate secretion [110]. In the α intercalated cells of the mouse cortical collecting duct, ANG II stimulated the secretion of H + into the lumen, which drove Cl -reabsorption via apical Cl -/HCO 3-exchange and generated a more favorable electrochemical gradient for epithelial Na + channel (ENaC)-mediated Na + reabsorption [111].…”
Section: Distal Nephronmentioning
confidence: 99%
“…Finally, a fluorescence-based intracellular pH recovery assay using isolated collecting ducts showed that cAMP increased functional protein secretion by these cells (97). Subsequent correlated functional and immunocytochemical studies have shown that the cAMP effect on proton secretion is mediated by both PKA and PKC, although the crosstalk between these two pathways remains to be dissected in detail (143).…”
Section: Soluble Adenylyl Cyclase Camp and V-atpase Regulation In Kmentioning
confidence: 99%